Heterologous prime–boost vaccination with adenoviral vector and protein nanoparticles induces both Th1 and Th2 responses against Middle East respiratory syndrome coronavirus. Issue 24 (7th June 2018) - Jung, Seo-Yeon; Kang, Kyung Won; Lee, Eun-Young; Seo, Dong-Won; Kim, Hong-Lim; Kim, Hak; Kwon, TaeWoo; Park, Hye-Lim; Kim, Hun; Lee, Sang-Myeong; Nam, Jae-Hwan
Highlights: Immunization with MERS spike protein nanoparticles induced only Th2-biased response. Heterologous prime-boost immunization induced both Th1 and Th2-biased responses. Our vaccination strategy showed the protective effect against MERS-CoV. Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a highly pathogenic and zoonotic virus with a fatality rate in humans of over 35%. Although several vaccine candidates have been developed, there is still no clinically available vaccine for MERS-CoV. In this study, we developed two types of MERS-CoV vaccines: a recombinant adenovirus serotype 5 encoding the MERS-CoV spike gene (Ad5/MERS) and spike protein nanoparticles formulated with aluminum (alum) adjuvant. Next, we tested a heterologous prime–boost vaccine strategy, which compared priming with Ad5/MERS and boosting with spike protein nanoparticles and vice versa, with homologous prime–boost vaccination comprising priming and boosting with either spike protein nanoparticles or Ad5/MERS. Although both types of vaccine could induce specific immunoglobulin G against MERS-CoV, neutralizing antibodies against MERS-CoV were induced only by heterologous prime–boost immunization and homologous immunization with spike protein nanoparticles. Interestingly, Th1 cell activation was induced by immunization schedules including Ad5/MERS, but not by those including only spike protein nanoparticles. Heterologous prime–boost vaccination regimens including Ad5/MERS elicited simultaneous Th1 and Th2 responses, but homologous prime–boost regimens did not. Thus, heterologous prime–boost may induce longer-lasting immune responses against MERS-CoV because of an appropriate balance of Th1/Th2 responses. However, both heterologous prime–boost and homologous spike protein nanoparticles vaccinations could provide protection from MERS-CoV challenge in mice. Our results demonstrate that heterologous immunization by priming with Ad5/MERS and boosting with spike protein nanoparticles could be an efficient prophylactic strategy against MERS-CoV infection.